Proportionality of the Determination of Criminal Sanctions in Law Number 23 of 2004 on the Elimination of Domestic Violence: Proporsionalitas Penetapan Ancaman Sanksi Pidana Dalam Undang-Undang No. 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga - Azizah, Nita Anisatul (Lex Renaissance, 2023)
Proportionality in the criminal sanctions formulation policy in this research is the criminal sanctions for perpetrators of criminal acts of violence against women which need to receive full attention from legislators in determining criminal sanctions policies. This is due to preventing violations of individual rights and as a barrier for legislators in imposing criminal sanctions for offenses. The focus of the problem in this research is the practice of developing violence against women in the family sphere during the Covid-19 pandemic and an analysis of the proportionality of determining the threat of criminal sanctions in Law no. 23 of 2004 on the Elimination of Domestic Violence. The type of research used is normative legal research. The approach used is conceptual and statutory. The research results showed that the level of violence in the domestic realm tends to be higher than in the public realm, as in 2021 the domestic realm experienced an increase of 4% compared to 2020. In 2020 violence against women was around 75%, while in 2021 it rose to 79% or 6,480 cases. The results of the proportionality analysis of criminal sanctions in the law are based on the principle of parity contained in ordinal proportionality, namely that a person is punished or sentenced in proportion to the level of seriousness of the crime or violation, reflecting the existence of parity, rank ordering, spacing of penalties from Articles 44 to 49.